Beyond traditional note-taking: Comparing the effects of collaboratively-generated versus instructor-provided notes on recall and writing performance - Fanguy, Mik (Australasian Journal of Educational Technology, 2025)
Note-taking is generally regarded as an effective learning strategy, but it is also cognitively demanding. Students often omit salient information in their notes due to the burden of trying to listen while writing down what they hear. Two alternative forms to traditional note-taking are online collaborative note-taking and instructor-provided notes. The former strategy allows students to work together online in small groups to share the burden of note-taking as well as the benefits of the collaborative document they produce together. The latter strategy involves the course instructor providing students with a complete set of notes, freeing students cognitively to listen and make connections with the lecture content. However, research on these two approaches remains sparse, and thus far, no study has compared their effects on learning performance. Therefore, the present study compared the learning performances of 161 students divided into two treatment conditions within a flipped learning environment: one where students took collaborative notes and another where students received notes provided by the instructor. Quiz scores showed no differences between the two conditions, but measures of both group and individual writing quality were significantly higher in the online collaborative note-taking condition than with the instructor-provided notes. Implications for practice or policy: To enhance students’ recall, instructors should provide notes to students. To bolster students’ ability to collaborate, instructors should have students take online collaborative notes. To enable students to improve and apply a skill, such as writing, instructors should have students take online collaborative notes.